Personal autonomy as a key factor of human self-determination - Liudmyla Serdiuk; Ivan Danyliuk; Galina Chaika (Social Welfare: Interdisciplinary Approach, 2018)
The article presents the research on psychological factors of personal autonomy as a self-determination need and as a component of psychological well-being. The analysis was carried out in two directions: within in the theory of self-determination and within the theory of psychological well-being.